Impact of nurse supervisor on social exclusion and counterproductive behaviour of employees - Kashif Ali; Satirenjit Kaur Johl (Cogent Business & Management, 2020)
This study aimed to examine how ostracism and narcissistic nursing supervisors affect the counterproductive work behaviour of junior nurses, with political skills as a moderator, in a country-specific context. This study achieved its objectives by reviewing the literature on ostracism, narcissism, counterproductive work behaviour, and political skills as well as the outcomes of relevant previous studies. The social exchange theory and conservation of resources theory were drawn upon to explain the relationships under study. An adapted questionnaire was used to gather responses using a5-point Likert scale. The obtained data were analysed using Smart-PLS 3. Ostracism and narcissistic nursing supervisors were found to contribute to the counterproductive work behaviour of nurses. The moderating roles of political skills on the proposed relationships were also assessed. Based on asample of junior nurses, the obtained results appeared to support the hypothesised relationships. Conclusively, when nurses encounter ostracism and narcissistic nursing supervisors, they are more likely to react with counterproductive work behaviour with alow level of political skills, and vice versa. The use of external self-reporting measure for narcissism produced more concise results. The dark aspects of human behaviour in the organisational and behavioural contexts were also revealed. Finally, the moderating role of political skills in the behavioural context was proved in this study.
Keywords: 650; Workplace ostracism; narcissism; counterproductive work behaviour; political skills